ILLNESS PERCEPTION DAN KEPATUHAN PENGOBATAN PADA PASIEN GAGAL GINJAL KRONIS DI SALATIGA - Stella Karlina Prabowo; Arthur Huwae (Psibernetika, 2022)
Chronic kidney failure is a progressive deviation of kidney function so that the body finds it difficult to maintain metabolic balance. Kidney failure can be treated by complying with the recommended treatment, this is one of the behaviors performed by patients in response to the problems they are experiencing, with one of the factors which affect adherence, namely illness perception. This study aims to determine whether or not there is a relationship between illness perception and medication adherence in patients with chronic kidney failure. Data was collected using quantitative methods with a correlational design. The participants involved were 48 patients with chronic kidney failure in Salatiga using the snowball sampling technique. The data was collected using the illness perception scale and the medication adherence scale. The results showed that there was a significant positive relationship between illness perception and medication adherence in patients with chronic kidney failure in Salatiga. This implies that illness perception is one of the factors that contribute to treatment adherence of chronic kidney failure patients in Salatiga